Relative Importance of Monetary Transmission Mechanism in Sri Lanka: An Empirical Investigation - Sooriyakumar, K.; Sivanathan, V.P.; Sireeranhan, A. (University of Jaffna, 2015)
This paper studies various monetary transmission channels in Sri Lanka to identify the more effective transmission mechanism and the policy rate that signals changes in monetary policy more effectively. The standard recursive Structural Vector Autoregression (SVAR) models are used to analyze monetary transmission mechanism. Monthly data from January 2005 to August 2013 were collected from central bank of Sri Lanka and IMF data base. SVAR model that we used consists of six endogenous variables and four exogenous variables. The six endogenous variables are Sri Lanka industrial production index, CPI, reserve money, policy rate (repo, average weighted money call rate, and t-bill), credit to private sector, and the nominal effective exchange rate (NEER). The four exogenous variables that affect endogenous variables are global oil price index, global food price index, U.S federal funds rate and U.S. industrial production index. To identify the effective transmission channel in Sri Lanka, we estimated the nine SVAR models with credit to private sector, policy rate, and nominal effective exchange rate (NEER) as exogenous variables as well as endogenous variables in the model separately, using three policy rates. Impulse responses of output to one standard deviation positive shock in reserve money in the nine SVAR models indicates that Credit channel is more effective transmission channel than interest rate and exchange rate channel in Sri Lanka and repo is the policy rate that signals the changes in monetary policy more effectively.
Keywords: Monetary transmission mechanism; Structural Vector Auto Regression; Endogenous; Exogenous variables